2021
DOI: 10.12911/22998993/137358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Air-Flow Rate and Biochar Addition on the Oxygen Concentration in Waste and Emitted Gases During Biostabilization of Undersized Fraction from Municipal Solid Waste

Abstract: Mechanical biological treatment of waste is still one of the most popular methods for mixed municipal waste treatment. The result of mechanical processing of waste is sorting out: the undersized fraction from municipal solid waste (UFMSW) with granulation below 80 mm, rich in biodegradable organic waste (mainly including food waste, paper, wood, etc.). UFMSW is treated in biological processes in order to reduce the negative environmental effect of this waste. Unfortunately, the processing is not neutral to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 28 publications
1
20
3
Order By: Relevance
“…The physical and chemical characteristics of the raw materials and input mixtures are presented in Malinowski [ 42 ]. According to data ( Table 1 ), the DM of UFMSW was 56.8 wt% and it increased with an increase in the dose of the biochar added to the waste.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The physical and chemical characteristics of the raw materials and input mixtures are presented in Malinowski [ 42 ]. According to data ( Table 1 ), the DM of UFMSW was 56.8 wt% and it increased with an increase in the dose of the biochar added to the waste.…”
Section: Resultsmentioning
confidence: 99%
“…The waste samples under study consisted of UFMSW exiting the mechanical treatment process (MSW treatment with a rotary screen, 80 mm opening size) at an MBT facility (MIKI Recykling Ltd.) in Kraków (Poland). The biochar used in the research is a material available commercially on the market and was obtained from coniferous woodchips as a result of pyrolysis in the thermalization energy recovery module at 550 °C for 30 min [ 29 , 42 ]. As Lehmann [ 43 ] and Jin et al [ 44 ] have reported, this temperature allows for obtaining biochar with the most favorable properties, i.e., high carbon content, cation exchange capacity, and a specific surface area, which are important in the biological methods of waste treatment and biochar application to soils [ 45 , 46 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations